Method for preparing silicon carbide ceramic with the aid of microorganisms and silicon carbide ceramic

CN122725858BActive Publication Date: 2026-10-27CHINA HUBEI LONGZHONG LABORATORY +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611193404.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-27
Estimated Expiration
2046-08-07

AI Technical Summary

Benefits of technology

[0053]该方法在泥坯中利用枯草芽孢杆菌在陈腐处理过程中代谢产生的胞外多糖和粘结剂协同配合,构建胞外多糖与粘结剂互穿双网络,通过陈腐处理后泥坯的粘度判断细菌的代谢程度,使泥坯具有较好的塑性变形能力。在泥坯排胶处理后细菌、胞外多糖和粘结剂发生热解可以为渗硅提供碳源,而且枯草芽孢杆菌、胞外多糖和粘结剂可以协同构建多级结构模板,其中枯草芽孢杆菌可以作为1μm~1.5μm的刚性生物模板,碳化后形成球形中空孔隙;胞外多糖凝胶网络则转化为纳米级多孔碳骨架,两者与粘结剂配合共同构成从微米到纳米的分级连通孔道,可以高效引导液态硅的渗透,有效降低残硅并促使残硅均匀分布,提升陶瓷整体性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122725858B_ABST
    Figure CN122725858B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of ceramic materials, and provides a method for preparing silicon carbide ceramics with the assistance of microbial aging and silicon carbide ceramics. The method comprises the following steps: mixing and kneading a mixture of materials including silicon carbide, carbon material, bacillus subtilis spore powder, nitrogen source nutrient agent, carbon source nutrient agent, binder, curing agent and solvent to obtain a green body; performing aging treatment on the green body, and then sequentially performing curing forming and degassing treatment to obtain a blank; and performing silicon infiltration treatment on the blank to obtain the silicon carbide ceramics. In the method, the extracellular polysaccharide formed by metabolism of bacillus subtilis during the aging treatment process and the binder form an interpenetrating network, hierarchical connected pores from microns to nanometers can be formed after the degassing treatment, the liquid silicon is efficiently guided to infiltrate, the residual silicon is effectively reduced and uniformly distributed, and the mechanical properties of the ceramics are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of ceramic materials technology, and in particular to a method for preparing silicon carbide ceramics with microbial aging assistance, and silicon carbide ceramics. Background Technology

[0002] Silicon carbide (SiC) ceramics are widely used in components such as bearings, heat exchangers, radiators, and turbine blades due to their excellent mechanical properties, high-temperature resistance, wear resistance, and corrosion resistance. In the reaction sintering process of silicon carbide, liquid or gaseous silicon is infiltrated into a porous preform containing a mixture of silicon carbide and a carbon source, and then reacted at high temperature to generate SiC, thus producing silicon carbide ceramics. This process offers advantages such as low sintering temperature and short sintering time.

[0003] In the process of preparing silicon carbide ceramics by reaction sintering, the binder in the green body is removed by pyrolysis to form silicon diffusion channels. However, the silicon diffusion channels formed by traditional organic binders may have problems such as excessively large pore size or uneven distribution. As a result, there is more residual silicon after silicon diffusion treatment and its distribution is uneven, which leads to a deterioration in the mechanical properties of silicon carbide ceramics. Summary of the Invention

[0004] Therefore, it is necessary to provide a method for preparing silicon carbide ceramics with the assistance of microbial aging, as well as silicon carbide ceramics, which can effectively reduce residual silicon in the material and promote the uniform distribution of residual silicon, thereby improving the mechanical properties of silicon carbide ceramics.

[0005] In a first aspect, this application provides a method for the microbial aging-assisted preparation of silicon carbide ceramics, comprising the following steps:

[0006] A clay blank is obtained by mixing and refining a mixture of silicon carbide, carbon materials, Bacillus subtilis spore powder, nitrogen source nutrients, carbon source nutrients, binder, curing agent and solvent; the mass ratio of silicon carbide in the mixture is 50% to 75%, and the mass ratio of Bacillus subtilis spore powder is 1% to 4% of the mass of silicon carbide;

[0007] After aging the clay blanks to achieve a viscosity of 200 Pa·s to 340 Pa·s, the clay blanks are then subjected to solidification and molding processes followed by adhesive removal to obtain the raw blanks.

[0008] Silicon infiltration treatment is performed on the green body to obtain silicon carbide ceramics.

[0009] In some embodiments, the method for preparing silicon carbide ceramics with microbial aging assistance satisfies at least one of the following conditions:

[0010] (1) The mixing and refining speed is 30 rpm to 42 rpm, and the time is 20 min to 60 min;

[0011] (2) The thickness of the clay blank is 2mm~3mm;

[0012] (3) The environmental conditions for aging treatment are as follows: temperature is 30℃~40℃, humidity is ≥90%RH, aging treatment time is 18h~40h, and oxygen volume concentration is 18%~22%;

[0013] (4) During the aging process, the clay bricks are laid on the screen;

[0014] (5) The pH of the clay blanks during the aging process is 6.5~7.5;

[0015] (6) The curing process adopts injection molding. The temperature of injection molding is 140℃~200℃, the holding time is 1h~10h, and the injection pressure is 0.1MPa~5MPa.

[0016] (7) The temperature of the glue removal treatment is 900℃~1100℃, the heat preservation time is 1h~4h, the heating rate is 1℃ / min~5℃ / min, and the atmosphere is a protective atmosphere.

[0017] In some embodiments, the method for preparing silicon carbide ceramics with microbial aging assistance satisfies at least one of the following conditions:

[0018] (1) Nitrogen source nutrients include at least one of peptone, yeast extract and ammonium sulfate;

[0019] (2) The nitrogen source nutrients include peptone and yeast extract, and the mass ratio of peptone to yeast extract is (5~8):(2~5).

[0020] (3) Carbon source nutrients include at least one of glucose and glycerol;

[0021] (4) Carbon materials include at least one of graphite, carbon powder and carbon black;

[0022] (5) The adhesive includes at least one of phenolic resin and epoxy resin;

[0023] (6) The curing agent includes at least one of hexamethylenetetramine and methylhexahydrophthalic anhydride;

[0024] (7) The solvent includes a first solvent and a second solvent. The first solvent is used to dissolve the binder and the curing agent. The first solvent includes ethylene glycol. The second solvent is used to dissolve the carbon source nutrient and the nitrogen source nutrient. The second solvent includes at least one of glycerol, polyethylene glycol and propylene glycol.

[0025] (8) Silicon carbide includes first silicon carbide and second silicon carbide; wherein the volume average particle size of the first silicon carbide is 0.5 μm to 5 μm, and the volume average particle size of the second silicon carbide is 20 μm to 100 μm; the mass ratio of the first silicon carbide to the second silicon carbide is 1:(1~4).

[0026] (9) The mass of the nitrogen source nutrient in the mixture shall be 60% to 150% of the mass of Bacillus subtilis spore powder;

[0027] (10) The mass of the carbon source nutrient in the mixture is 80% to 200% of the mass of Bacillus subtilis spore powder;

[0028] (11) The mass of carbon material in the mixture is 12% to 24% of the mass of silicon carbide;

[0029] (12) The mass of the binder in the mixture is 3.5% to 11.5% of the mass of silicon carbide;

[0030] (13) The mass of the curing agent in the mixture is 9% to 12% of the mass of the adhesive.

[0031] In some embodiments, the mixture also contains a lubricant.

[0032] In some implementations, the lubricant satisfies at least one of the following conditions:

[0033] (1) The lubricant includes at least one of paraffin wax, stearic acid and oleic acid;

[0034] (2) The mass percentage of lubricant in the mixture is 1% to 3%.

[0035] In some embodiments, the silicon infiltration process includes: laying silicon particles on a green blank, heating and infiltrating them, and then cooling to obtain silicon carbide ceramics.

[0036] In some embodiments, the silicon infiltration process satisfies at least one of the following conditions:

[0037] (1) The volume average particle size of silicon grains is 0.5 mm to 5 mm;

[0038] (2) The amount of silicon particles added is 1 to 1.5 times the mass of the green blank;

[0039] (3) During the silicon infiltration process, the heating temperature is 1500℃~1800℃, the holding time is 1h~6h, the heating rate is 2℃ / min~10℃ / min, and the vacuum degree is ≤50Pa.

[0040] In some embodiments, the method for preparing the clay blank includes:

[0041] A mixed powder is obtained by mixing silicon carbide, carbon materials and Bacillus subtilis spore powder;

[0042] A mixed solution is obtained by mixing a first mixture containing a binder, a curing agent, and a first solvent with a second mixture containing a nitrogen source nutrient, a carbon source nutrient, and a second solvent.

[0043] After spraying nutrient solution into the mixed powder, a mixed solution is added to mix and knead the mud to obtain mud blanks.

[0044] In some embodiments, the method for preparing the clay blank satisfies at least one of the following conditions:

[0045] (1) The mixture is formed by ball milling. The ball-to-material ratio is (5~10):1, the ball milling speed is 100rpm~150rpm, and the time is 4h~8h.

[0046] (2) The first mixture contains 45% to 50% by mass of binder and 4.0% to 5.5% by mass of curing agent, and the first solvent includes ethylene glycol;

[0047] (3) The second mixture contains 10% to 15% nitrogen source nutrients and 15% to 20% carbon source nutrients by mass. The second solvent includes at least one of glycerol, polyethylene glycol and propylene glycol.

[0048] (4) The nutrient solution consists of water, glycerol, and peptone in a mass ratio of (2.90~2.99):(6.90~6.99):(0.01~0.05);

[0049] (5) The volume of nutrient solution sprayed per gram of mixed powder is 0.05 mL to 0.07 mL;

[0050] (6) The average volumetric diameter of the droplets formed by spraying nutrient solution is 5 μm to 50 μm.

[0051] Secondly, this application provides a silicon carbide ceramic obtained by the method of microbial aging-assisted preparation of silicon carbide ceramics as described in the first aspect.

[0052] Compared with traditional technologies, this application has at least the following beneficial effects:

[0053] This method utilizes the synergistic effect of extracellular polysaccharides produced by Bacillus subtilis during aging and binders in the clay blank to construct an interpenetrating double network of extracellular polysaccharides and binders. The viscosity of the clay blank after aging is used to determine the degree of bacterial metabolism, thus giving the clay blank better plastic deformation ability. After the clay blank is debonded, the pyrolysis of bacteria, extracellular polysaccharides, and binders can provide a carbon source for silica infiltration. Moreover, Bacillus subtilis, extracellular polysaccharides, and binders can synergistically construct a multi-level structural template. Bacillus subtilis can serve as a rigid biological template of 1μm~1.5μm, forming spherical hollow pores after carbonization; the extracellular polysaccharide gel network is transformed into a nanoscale porous carbon skeleton. Together with the binder, they form a hierarchical interconnected channel from micrometer to nanometer, which can efficiently guide the infiltration of liquid silicon, effectively reduce residual silicon and promote its uniform distribution, thereby improving the overall performance of the ceramic. Attached Figure Description

[0054] To more clearly illustrate the technical solutions in the embodiments and examples of this application, and to more completely understand this application and its beneficial effects, the accompanying drawings used in the description of the embodiments or examples will be briefly introduced below. Obviously, the drawings described below are merely some embodiments of this application. Those skilled in the art can obtain other drawings based on these drawings without any creative effort.

[0055] Figure 1 This is a schematic flowchart of a method for preparing silicon carbide ceramics with microbial aging assistance provided in one embodiment of this application.

[0056] Figure 2 This is a schematic flowchart of a method for preparing clay blanks according to one embodiment of this application;

[0057] Figure 3 The images shown are SEM images of the silicon carbide ceramics prepared in Examples 2, 1, 2 and 3 of this application. Detailed Implementation

[0058] The present application will be further described in detail below with reference to the embodiments and examples. These embodiments and examples are for illustrative purposes only and are not intended to limit the scope of the present application. The purpose of providing these embodiments and examples is to enable a more thorough and comprehensive understanding of the disclosure of the present application. It should also be understood that the present application can be implemented in many different forms and is not limited to the embodiments and examples described herein. Those skilled in the art can make various modifications or alterations without departing from the spirit of the present application, and the equivalent forms obtained also fall within the protection scope of the present application. Furthermore, numerous specific details are set forth in the following description to provide a fuller understanding of the present application. It should be understood that the present application can be implemented without one or more of these details.

[0059] In this application, "optionally," "optionally," and "optional" mean that something is optional, that is, it means that it is selected from either "with" or "without." If there are multiple "optional" entries in a technical solution, unless otherwise specified, and there are no contradictions or mutual constraints, each "optional" entry shall be independent.

[0060] In this application, the terms "first aspect," "second aspect," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "first aspect," "second aspect," etc., serve only as a non-exhaustive enumeration and should be understood not to constitute a closed limitation on quantity.

[0061] The "Bacillus subtilis spore powder" in this application is a solid microbial preparation made from the dormant spores of Bacillus subtilis as the main active ingredient, through processes such as fermentation, concentration, and adsorption (e.g., corn starch). The Bacillus subtilis spore powder contains ≥10 viable bacteria. 9 CFU / g, Bacillus subtilis has the biopreservation number CICC10089, and its main metabolism forms EpsA-O extracellular polysaccharide.

[0062] In traditional techniques, phenolic resin and other binders are used to form silicon infiltration channels in the green body after debinding. However, during the debinding process, phenolic resin creates numerous micropores with poor dispersion and connectivity within the green body, making it difficult to achieve sufficient wetting during silicon infiltration. Furthermore, the carbon material formed after phenolic resin carbonization often exists as encapsulated particles with low graphitization and uneven dispersion, making it difficult to maintain continuous flow through the pores and easily causing pore closure, thus affecting the mechanical properties of silicon carbide ceramics.

[0063] The first aspect of this application provides a method for the microbial aging-assisted preparation of silicon carbide ceramics, such as... Figure 1 As shown, it includes the following steps:

[0064] A clay blank is obtained by mixing and refining a mixture of silicon carbide, carbon materials, Bacillus subtilis spore powder, nitrogen source nutrients, carbon source nutrients, binder, curing agent and solvent; the mass ratio of silicon carbide in the mixture is 50% to 75%, and the mass ratio of Bacillus subtilis spore powder is 1% to 4% of the mass of silicon carbide;

[0065] After aging the clay blanks to achieve a viscosity of 200 Pa·s to 340 Pa·s, the clay blanks are then subjected to solidification and molding processes followed by adhesive removal to obtain the raw blanks.

[0066] Silicon infiltration treatment is performed on the green body to obtain silicon carbide ceramics.

[0067] Wherein, without limitation, the mass percentage of silicon carbide in the mixture can be, for example, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70%, 71%, 72%, 73%, 74%, or 75%. The mass percentage of Bacillus subtilis spore powder is 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, 3.0%, 3.2%, 3.4%, 3.6%, 3.8%, or 4.0% of the mass of silicon carbide. The above-selected amounts of silicon carbide and Bacillus subtilis spore powder ensure the plastic deformation capacity of the clay body and allow the extracellular polysaccharides formed by bacterial metabolism to form an interpenetrating double network of extracellular polysaccharides and binders.

[0068] Optionally, the mass percentage of Bacillus subtilis spore powder in the mixture is 1% to 2%, for example, it can be 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9% or 2.0%.

[0069] Non-limitingly, the viscosity of the clay blank can be, for example, 200 Pa·s, 210 Pa·s, 220 Pa·s, 230 Pa·s, 240 Pa·s, 250 Pa·s, 260 Pa·s, 270 Pa·s, 280 Pa·s, 290 Pa·s, 300 Pa·s, 310 Pa·s, 320 Pa·s, 330 Pa·s, or 340 Pa·s. This viscosity refers to the viscosity obtained by rotational rheology testing at 25°C. This method can determine the degree of spore metabolism by controlling the viscosity of the clay blank after aging, thereby enabling the spores to secrete an appropriate amount of extracellular polysaccharides to synergistically form an interpenetrating double network with the binder. If the viscosity of the clay blank after aging is relatively low, it indicates that the aging process is poor, with less extracellular polysaccharide produced by spore metabolism, making it difficult to form an interpenetrating double network. If the viscosity of the clay blank after aging is relatively high, it indicates that more extracellular polysaccharide is produced by spore metabolism, making the sample difficult to press into shape and resulting in problems such as residual carbon and more pores after silica infiltration.

[0070] In some embodiments, silicon carbide comprises a first silicon carbide and a second silicon carbide. Optionally, the volume average particle size of the first silicon carbide is 0.5 μm to 5 μm, for example, it can be 0.5 μm, 1.0 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm; the volume average particle size of the second silicon carbide is 20 μm to 100 μm, for example, it can be 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm; the mass ratio of the first silicon carbide to the second silicon carbide is 1:(1~4), for example, it can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5 or 1:4.

[0071] By employing the aforementioned gradation strategy in the raw materials, silicon carbide can achieve precise optimization of particle arrangement at the microscale. The relatively larger second silicon carbide particles form the main framework, while the relatively smaller first silicon carbide particles penetrate into the framework, fully filling the gaps between the second silicon carbide particles. This reduces porosity and significantly increases packing density, ensuring the structural density of the cured green body and enhancing its mechanical strength. Furthermore, it limits the penetration channels of the silicon melt during the silicon infiltration process, effectively reducing residual silicon content. Since silicon and silicon carbide have significantly different coefficients of thermal expansion, reducing residual silicon in ceramic materials can significantly alleviate interfacial stress caused by temperature changes, achieving a comprehensive improvement in the material's overall performance.

[0072] In some embodiments, the mass of the nitrogen source nutrient in the mixture is 60% to 150% of the mass of Bacillus subtilis spore powder, for example, it can be 60%, 65%, 70%, 75%, 80%, 90%, 100%, 110%, 120%, 130%, 140%, or 150%. Optionally, the mass percentage of the nitrogen source nutrient in the mixture is 1% to 2.5%.

[0073] The nitrogen source nutrient can be made of organic or inorganic materials, as long as it meets the metabolic needs of Bacillus subtilis to form extracellular polysaccharides. In some embodiments, the nitrogen source nutrient includes at least one of peptone, yeast extract, and ammonium sulfate. Peptone is a mixture of soluble polypeptides and amino acids obtained by partial hydrolysis of proteins with acid, alkali, or proteases. Its molecular weight is typically between 500 Da and 3000 Da, and it is rich in organic nitrogen sources, vitamins, sugars, and minerals, widely used as a core nitrogen source component in microbial culture media. Optionally, the peptone can be at least one of animal-derived peptone and plant-derived peptone; for example, animal-derived peptone can be trypsin, beef peptone, bone peptone, gelatin peptone, casein peptone, or blood meal peptone. Plant-derived peptone can be soybean peptone, wheat peptone, or potato peptone. Yeast extract is a soluble concentrate made from edible yeast (such as brewer's yeast) through processes such as autolysis, enzymatic hydrolysis, separation, and concentration. It mainly contains polypeptides, free amino acids, B vitamins, nucleotides, and minerals. Its CAS number is 8013-01-2.

[0074] Optionally, the nitrogen source nutrient includes peptone and yeast extract, with the mass ratio of peptone to yeast extract being (5~8):(2~5), for example, 5.0:5.0, 5.5:4.5, 6.0:4.0, 6.5:3.5, 7.0:3.0, 7.5:2.5 or 8.0:2.0.

[0075] In some embodiments, the mass of the carbon source nutrient in the mixture is 80% to 200% of the mass of Bacillus subtilis spore powder, for example, it can be 80%, 100%, 120%, 140%, 160%, 180% or 200%.

[0076] In some embodiments, the carbon source nutrient includes at least one of glucose and glycerol.

[0077] In some embodiments, the mass of carbon material in the mixture is 12% to 24% of the mass of silicon carbide, for example, it can be 12%, 14%, 16%, 18%, 20%, 22%, or 24%. Optionally, the mass percentage of carbon material in the mixture is 9% to 15%, for example, it can be 9%, 10%, 11%, 12%, 13%, 14%, or 15%.

[0078] In some embodiments, the carbon material includes at least one of graphite, carbon powder, and carbon black. For example, nano-carbon powder or spherical carbon powder may be used.

[0079] In some embodiments, the mass of the binder in the mixture is 3.5% to 11.5% of the mass of silicon carbide, for example, 3.5%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, or 11.5%. Optionally, the mass percentage of the binder in the mixture is 5.0% to 7.5%, for example, 5.0%, 5.5%, 6.0%, 6.5%, 7.0%, or 7.5%.

[0080] In some embodiments, the mass of the curing agent is 9% to 12% of the mass of the adhesive, for example, it can be 9%, 9.5%, 10%, 10.5%, 11%, 11.5% or 12%.

[0081] In some embodiments, the binder includes at least one of phenolic resin and epoxy resin. For example, the phenolic resin has a molecular weight of 800-2500. The curing agent includes at least one of hexamethylenetetramine and methylhexahydrophthalic anhydride.

[0082] In some embodiments, the solvent includes a first solvent and a second solvent. The first solvent is used to dissolve the binder and the curing agent, and the first solvent includes ethylene glycol. The second solvent is used to dissolve the carbon source nutrient and the nitrogen source nutrient, and the second solvent includes at least one of glycerol, polyethylene glycol, and propylene glycol.

[0083] Optionally, the second solvent includes glycerol. Glycerol can not only dissolve and disperse the nitrogen source nutrient, but also act as a carbon source nutrient and a plasticizer, effectively ensuring the molding of the preform and the complete silicon diffusion reaction. It is understood that glycerol can simultaneously function as a carbon source nutrient and a solvent.

[0084] Optionally, the solvent includes at least one of polyethylene glycol and propylene glycol. Polyethylene glycol and propylene glycol are difficult to use as carbon sources for bacterial growth, necessitating the introduction of additional carbon sources to meet the strain's growth requirements. Carbon sources can be added according to the strain's growth needs.

[0085] Suitable additives may be added to the clay body according to the compatibility and thermal stability of the silicon carbide clay body system. In some embodiments, the mixture also contains a lubricant. For example, the lubricant includes at least one selected from paraffin wax, stearic acid, and oleic acid. Optionally, the mass percentage of lubricant in the mixture is 1% to 3%, for example, it may be 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.2%, 2.4%, 2.6%, 2.8%, or 3.0%.

[0086] In some embodiments, such as Figure 2 As shown, the method for preparing clay blanks includes:

[0087] A mixed powder is obtained by mixing silicon carbide, carbon materials and Bacillus subtilis spore powder;

[0088] A mixed solution is obtained by mixing a first mixture containing a binder, a curing agent, and a first solvent with a second mixture containing a nitrogen source nutrient, a carbon source nutrient, and a second solvent.

[0089] After spraying nutrient solution into the mixed powder, a mixed solution is added to mix and knead the mud to obtain a mud blank. Optionally, the viscosity of the mud blank obtained by mixing and kneading is 50 Pa·s to 70 Pa·s, for example, 50 Pa·s, 55 Pa·s, 60 Pa·s, 65 Pa·s or 70 Pa·s.

[0090] In some embodiments, ball milling is used to mix the materials to form a mixed powder. Optionally, the ball-to-material ratio in the ball mill is (5~10):1, for example, 5:1, 6:1, 7:1, 8:1, 9:1, or 10:1; the ball milling speed is 100rpm~150rpm, for example, 100rpm, 110rpm, 120rpm, 130rpm, 140rpm, or 150rpm; the ball milling time is 4h~8h, for example, 4h, 5h, 6h, 7h, or 8h. The ball milling medium can be silicon carbide grinding balls with a particle size of 2mm~12mm.

[0091] The ball milling method described above is used to uniformly mix silicon carbide, carbon materials, and Bacillus subtilis spore powder, allowing the spores to adhere to the surface of the silicon carbide in a monodisperse state. This ensures that microbial metabolites are uniformly dispersed in the clay blank, guaranteeing the size and connectivity of the silicon infiltration channels. Furthermore, the silicon carbide and carbon materials can be thoroughly mixed at the nano / micro scale, ensuring uniform distribution of the carbon materials during subsequent reaction and sintering, and avoiding incomplete local reactions or excessive residual silicon accumulation.

[0092] In some embodiments, the mixed solution is obtained by centrifugal stirring. Optionally, the centrifugal stirring speed is 1000 rpm to 2000 rpm, and the time is 2 min to 15 min.

[0093] In some embodiments, the first mixture contains 45% to 50% by mass of the binder, for example, 45%, 46%, 47%, 48%, 49%, or 50%. The first mixture contains 4.0% to 5.5% by mass of the curing agent.

[0094] In some embodiments, the second mixture contains 10% to 15% nitrogen source nutrients by mass, for example, 10%, 11%, 12%, 13%, 14%, or 15%. The second mixture contains 15% to 20% carbon source nutrients by mass, for example, 15%, 16%, 17%, 18%, 19%, or 20%.

[0095] The second mixture is obtained by mixing the nitrogen source nutrient, the carbon source nutrient, and the second solvent. For example, the nitrogen source nutrient, the carbon source nutrient, and the second solvent are heated and stirred to dissolve them at a temperature of 40°C to 65°C.

[0096] In some embodiments, the nutrient solution comprises water, glycerol, and peptone in a mass ratio of (2.90~2.99):(6.90~6.99):(0.01~0.05).

[0097] In some embodiments, the volume of nutrient solution sprayed per gram of mixed powder is 0.05 mL to 0.07 mL, for example, 0.050 mL, 0.055 mL, 0.060 mL, 0.065 mL or 0.070 mL.

[0098] In some embodiments, the volume average particle size of the droplets formed by spraying the nutrient solution is 5 μm to 50 μm, for example, it can be 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm or 50 μm. Optionally, the mixed powder is placed in a rotary mixer, and the nutrient solution is sprayed during operation.

[0099] During the preparation of this clay blank, by spraying nutrient solution into the mixed powder, a microscopic water film can be formed on the surface of the spores. Combined with aging treatment under high humidity, it can provide the basic conditions for spore germination and metabolic activities to produce extracellular polysaccharides, thereby forming a bio-organic gel network in the clay blank where extracellular polysaccharides and binders work synergistically.

[0100] In some embodiments, the mixing and refining speed is 30 rpm to 42 rpm, for example, 30 rpm, 32 rpm, 34 rpm, 36 rpm, 38 rpm, 40 rpm, or 42 rpm. The time is 20 min to 60 min, for example, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, or 60 min.

[0101] In some embodiments, the thickness of the clay block is 2mm to 3mm, for example, 2.0mm, 2.1mm, 2.2mm, 2.3mm, 2.4mm, 2.5mm, 2.6mm, 2.7mm, 2.8mm, 2.9mm, or 3.0mm. Controlling the thickness of the clay block as described above ensures sufficient internal oxygen supply, guaranteeing the metabolic rate of the spores. If the clay block is relatively thick, it may cause insufficient internal oxygen supply, leading to slow or stopped spore metabolism. If the clay block is relatively thin, initial spreading is more difficult and the clay block is harder to shape.

[0102] Alternatively, the lubricant can be added to the mixed solution to disperse it evenly.

[0103] In some embodiments, the environmental conditions for aging treatment meet the following requirements: temperature of 30°C to 40°C, humidity ≥90%RH, aging time of 18h to 40h, and oxygen volume concentration of 18% to 22%. For example, the aging temperature can be 30°C, 31°C, 32°C, 33°C, 34°C, 35°C, 36°C, 37°C, 38°C, 39°C, or 40°C. The humidity can be 90%RH, 91%RH, 92%RH, 93%RH, 94%RH, 95%RH, 96%RH, 97%RH, 98%RH, or 99%RH. The aging time can be 18h, 20h, 22h, 24h, 26h, 28h, 30h, 32h, 34h, 36h, 38h, or 40h. The volume concentration of oxygen can be, for example, 18.0%, 18.5%, 19.0%, 19.5%, 20.0%, 20.5%, 21.0%, 21.5%, or 22.0%.

[0104] Understandably, appropriate aging environmental parameters can be selected based on the viscosity of the aging clay after aging to ensure that the Bacillus subtilis spores secrete an adequate amount of extracellular polysaccharides. For example, aging under the conditions described above can result in a better spore germination rate and metabolic rate for Bacillus subtilis spores, promoting the production of extracellular polysaccharides and their formation of an interpenetrating network structure with the binder. Conversely, relatively high or low temperatures may slow down the metabolism of the strain, requiring a longer aging time; relatively low humidity may result in a low spore germination rate, leading to insufficient extracellular polysaccharide production.

[0105] In some embodiments, the clay blanks are laid on a screen during the aging process. Optionally, the screen aperture is 0.5 mm to 1 mm. In this embodiment, the clay blanks are laid on a screen, utilizing the screen's permeability to ensure sufficient dissolved oxygen inside the clay blanks.

[0106] In some embodiments, the pH of the clay blanks during aging is 6.5 to 7.5, for example, it can be 6.5, 6.6, 6.7, 6.8, 6.9, 7.0, 7.1, 7.2, 7.3, 7.4 or 7.5.

[0107] In some embodiments, the curing process employs injection molding, with the injection molding temperature ranging from 140°C to 200°C, for example, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 185°C, 190°C, 195°C, or 200°C; the holding time is from 1 hour to 10 hours, for example, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours; and the injection pressure is from 0.1 MPa to 5 MPa, for example, 0.1 MPa, 0.5 MPa, 1.0 MPa, 1.5 MPa, 2.0 MPa, 2.5 MPa, 3.0 MPa, 3.5 MPa, 4.0 MPa, 4.5 MPa, or 5.0 MPa.

[0108] In some embodiments, the temperature for the debinding process is 900℃~1100℃, for example, 900℃, 920℃, 940℃, 960℃, 980℃, 1000℃, 1020℃, 1040℃, 1060℃, 1080℃, or 1100℃; the holding time is 1h~4h, for example, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, or 4.0h; the heating rate is 1℃ / min~5℃ / min, for example, 1.0℃ / min, 1.5℃ / min, 2.0℃ / min, 2.5℃ / min, 3.0℃ / min, 3.5℃ / min, 4.0℃ / min, 4.5℃ / min, or 5.0℃ / min; and the atmosphere is a protective atmosphere. The protective atmosphere refers to a gas that does not react with the raw materials, such as nitrogen or argon.

[0109] In some embodiments, the silicon infiltration process includes: laying silicon grains on a green blank, heating and infiltrating, and then cooling to obtain silicon carbide ceramic.

[0110] In some embodiments, the volume average particle size of the silicon grains is 0.5 mm to 5 mm, for example, it can be 0.5 mm, 1.0 mm, 1.5 mm, 2.0 mm, 2.5 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm or 5.0 mm.

[0111] In some embodiments, the amount of silicon particles added is 1 to 1.5 times the mass of the preform, for example, it can be 1.0 times, 1.1 times, 1.2 times, 1.3 times, 1.4 times or 1.5 times.

[0112] In some embodiments, the heating temperature during the silicon infiltration process is 1500℃~1800℃, for example, 1500℃, 1530℃, 1560℃, 1590℃, 1620℃, 1650℃, 1680℃, 1710℃, 1740℃, 1770℃, or 1800℃; the holding time is 1h~6h, for example, 1h, 2h, 3h, 4h, 5h, or 6h. The heating rate is 2℃ / min~10℃ / min, for example, 2℃ / min, 3℃ / min, 4℃ / min, 5℃ / min, 6℃ / min, 7℃ / min, 8℃ / min, 9℃ / min, or 10℃ / min; the vacuum degree is ≤50Pa, for example, 1Pa, 5Pa, 10Pa, 15Pa, 20Pa, 25Pa, 30Pa, 35Pa, 40Pa, 45Pa, or 50Pa.

[0113] The second aspect of this application provides a silicon carbide ceramic, which is obtained by the method of microbial aging-assisted preparation of silicon carbide ceramic as described in the first aspect.

[0114] In some embodiments, the silicon carbide ceramic is composed of interlocking and tightly packed α-SiC particles. This structure promotes the uniformity of Si phase distribution, reduces residual silicon content and size, and then β-SiC formed during the silicon infiltration process fills the gaps between the α-SiC particles, ensuring good continuity of the silicon carbide phase and significantly enhancing the mechanical properties of the ceramic material.

[0115] The embodiments of this application will be described in detail below with reference to examples. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of this application. For experimental methods in the following embodiments where specific conditions are not specified, please refer to the guidelines given in this application, or follow experimental manuals or conventional conditions in the art, or follow the conditions recommended by the manufacturer, or refer to experimental methods known in the art.

[0116] In the following examples and comparative examples, the bio-preservation number of Bacillus subtilis spore powder is CICC 10089, which comes from the China Industrial Microbial Culture Collection Center.

[0117] The phenolic resin, designated as type 2132, was purchased from Dongguan Tuoguang Electromechanical Technology Co., Ltd.

[0118] The peptone powder, brand name NR210020, was purchased from Noborride Technology. The yeast extract, brand name YZ-212750, was also purchased from Noborride Technology.

[0119] Example 1

[0120] This embodiment provides a method for preparing silicon carbide ceramics with microbial aging assistance, including the following steps:

[0121] S1. Weigh out 25.5g of silicon carbide, 4.5g of graphite powder, 0.41g of Bacillus subtilis spore powder, 6g of the first mixture, 4.08g of the second mixture, and 0.3g of paraffin wax. The silicon carbide used is a first silicon carbide with a volume average particle size of 5μm and a second silicon carbide with a volume average particle size of 50μm, in a mass ratio of 4:6.

[0122] The first mixture comprises 45% phenolic resin, 5% hexamethylenetetramine, and 50% ethylene glycol by mass. The second mixture comprises 10% nitrogen source nutrient, consisting of peptone powder and yeast extract in a 1:1 mass ratio, with the remainder being glycerol. 20% of the glycerol is used as a carbon source nutrient, and the remaining 80% as a solvent. The second mixture is obtained by dissolving peptone powder and yeast extract in glycerol at 60°C with stirring.

[0123] S2. Add silicon carbide grinding balls with particle sizes of 2 mm and 6 mm to silicon carbide, graphite powder and Bacillus subtilis spore powder, and perform dry ball milling at a speed of 120 rpm for 4 hours with a ball-to-material ratio of 5:1; wherein the mass ratio of 2 mm silicon carbide grinding balls to 6 mm silicon carbide grinding balls is 3:7.

[0124] The first mixture, the second mixture, and paraffin were centrifuged and stirred at 2000 rpm for 10 minutes to obtain a gel-like mixed solution.

[0125] S3. The mixed powder is placed in a rotary mixer. At a speed of 45 rpm, 2 mL of nutrient solution is sprayed into the mixed powder at a rate of 0.5 mL / min. The volume average particle size of the sprayed droplets is 20 μm. The nutrient solution consists of glycerol, water, and peptone powder in a mass ratio of 2.99:6.99:0.02. After the nutrient solution is sprayed, the mixed solution is added, and the mixture is kneaded at 35 rpm for 45 min to obtain a clay blank.

[0126] S4. The clay blanks, with a thickness of 2mm to 3mm, were spread evenly on a stainless steel sieve with a mesh size of 0.5mm and placed in a ventilated environment at a temperature of 37±2℃, humidity >95%RH, and oxygen volume concentration of 20% for 24 hours of aging, resulting in clay blanks with a viscosity of 247.1 Pa·s. During the aging process, the pH of the clay blanks was measured to be 7.1 at the beginning of the aging process, 6.8 after 12 hours of aging, and 7.0 after the aging process was completed.

[0127] S5. Place the aged clay blank in a mold for injection molding and curing. The heating temperature for injection molding and curing is 180℃, the injection pressure is 2MPa, and the holding time is 2h. Then, raise the temperature to 1000℃ at a rate of 1℃ / min and perform debinding treatment for 1h under an argon atmosphere to obtain the raw blank.

[0128] S6. Place the above-mentioned green blank in a graphite crucible and spread a layer of silicon particles with an average volume diameter of 2 mm. The amount of silicon particles added is 1.5 times the mass of the green blank. Then, raise the temperature to 1550℃ at a heating rate of 5℃ / min and heat and infiltrate under a vacuum of 5 Pa for 2 hours. After cooling, grind and polish to remove the residual silicon layer on the surface to obtain silicon carbide ceramic.

[0129] Example 2

[0130] Silicon carbide ceramics were prepared using a method essentially the same as in Example 1, except that in step S1, 25.5 g of silicon carbide, 4.5 g of graphite powder, 0.5 g of Bacillus subtilis spore powder, 6 g of the first mixture, 3 g of the second mixture, and 0.5 g of paraffin were weighed. After aging, a clay blank with a viscosity of 283.6 Pa·s was obtained. During the aging process, the pH of the clay blank was measured to be 7.1 at the beginning of aging, 6.9 after 12 hours of aging, and 7.1 after the end of aging.

[0131] Example 3

[0132] Silicon carbide ceramics were prepared using a method essentially the same as in Example 1, except that in step S1, 25.5 g of silicon carbide, 4.5 g of graphite powder, 0.93 g of Bacillus subtilis spore powder, 6 g of the first mixture, 9.31 g of the second mixture, and 0.3 g of paraffin were weighed. After aging, a clay blank with a viscosity of 332.8 Pa·s was obtained. During the aging process, the pH of the clay blank was measured to be 7.1 at the beginning of aging, 7.0 after 12 hours of aging, and 7.3 after the end of aging.

[0133] Comparative Example 1

[0134] Silicon carbide ceramics were prepared using a method essentially the same as in Example 2, except that the aging time in step S4 was 12 hours, and a clay blank with a viscosity of 95.2 Pa·s was obtained after aging. During the aging process, the pH of the clay blank was measured to be 7.1 at the beginning of the aging process, 6.6 after 6 hours of aging, and 7.0 after the aging process was completed.

[0135] Comparative Example 2

[0136] Silicon carbide ceramics were prepared using a method essentially the same as in Example 2, except that the aging time in step S4 was 36 hours, and a clay blank with a viscosity of 359.4 Pa·s was obtained after aging. During the aging process, the pH of the clay blank was measured to be 7.1 at the beginning of the aging process, 7.0 after 18 hours of aging, and 7.2 after the aging process was completed.

[0137] Comparative Example 3

[0138] S1. Weigh out 25.5g of silicon carbide, 4.5g of graphite powder, 6g of the first mixture, 0.3g of the second mixture, and 0.3g of paraffin wax. The compositions of silicon carbide, the first mixture, and the second mixture are the same as in Example 1.

[0139] S2. Add silicon carbide ball milling beads with particle sizes of 2 mm and 6 mm and ethanol to silicon carbide and graphite powder, and perform dry ball milling at 150 rpm for 4 hours with a ball-to-powder ratio of 5:1. After ball milling, the powder is vacuum dried at 80°C for 24 hours and then sieved to obtain a mixed powder. The mass ratio of 2 mm silicon carbide ball milling beads to 6 mm silicon carbide ball milling beads is 3:7. The mass of ethanol is 70% of the total mass of silicon carbide and graphite powder.

[0140] S3. Glycerin and paraffin are added to the first mixture to obtain a mixed solution. The above mixed powder is added to the mixed solution and mixed and kneaded at a speed of 35 r / min to obtain a clay blank. The viscosity of the clay blank is 63.7 Pa·s.

[0141] S4. Place the above-mentioned clay blank into a mold for injection molding and curing. The heating temperature for injection molding and curing is 150℃, the injection pressure is 2MPa, and the time is 2h. Then, raise the temperature to 1000℃ at a heating rate of 1℃ / min and perform debinding treatment for 1h under an argon atmosphere to obtain the raw blank.

[0142] S5. Place the above-mentioned green blank into a graphite crucible and spread a layer of silicon with an average volume particle size of 2 mm. The amount of silicon particles added is 1.5 times the mass of the green blank. Then, heat the temperature to 1550℃ at a heating rate of 5℃ / min and heat and infiltrate for 2 hours under a vacuum of 5 Pa. After cooling, grind and polish to remove the residual silicon layer on the surface to obtain silicon carbide ceramic.

[0143] The silicon carbide ceramics prepared in the above embodiments and comparative examples were subjected to performance tests, including:

[0144] Bulk density: The bulk density of the ceramic material is measured by Archimedes' displacement method and calculated using the following formula:

[0145]

[0146] In the formula, ρ represents the bulk density of the ceramic material, m1 represents the dry weight of the ceramic material sample used for testing (in g), m2 represents the weight of the ceramic material sample floating in water (in g), and ρ0 represents the bulk density of deionized water (in g / cm³). 3 .

[0147] Porosity: The porosity of ceramic materials is measured by Archimedes' displacement method and calculated using the following formula:

[0148]

[0149] In the formula, P is the open porosity of the ceramic material, in %; m1 represents the dry weight of the ceramic material test sample, in g; m2 represents the weight of the ceramic material test sample floating in water, in g; and m3 represents the wet weight of the ceramic material test sample saturated in air, in g.

[0150] Residual silicon content: The residual silicon content of ceramic materials was measured using the hydrofluoric acid immersion method and calculated using the following formula:

[0151]

[0152] In the formula, Wt represents the residual silicon content of the ceramic material, in %; w1 represents the weight of the ceramic material sample before immersion, in g; and w2 represents the weight of the ceramic material sample after immersion, in g.

[0153] Bending strength: Tested using a universal testing machine according to GB / T 6569-2006 Test Method for Bending Strength of Fine Ceramics.

[0154] The test results are shown in Table 1.

[0155] Table 1

[0156]

[0157] As can be seen from the table above:

[0158] Example 2 is compared with Comparative Examples 1-3, and in combination with Figure 3 Under the same aging conditions, the aging time of Comparative Example 1 was shorter, resulting in insufficient production of EpsA-O extracellular polysaccharides, leading to insufficient silica infiltration channels. Figure 3 Comparative Example 1 exhibits excessive porosity, resulting in an excessively high density in the green body, which negatively impacts ceramic properties. Simultaneously, the green body retains a significant amount of nitrogen-based nutrients and glycerol, affecting its shaping and sintering. Comparative Example 2, with its longer aging time, produces a greater amount of EpsA-O extracellular polysaccharides, leading to the formation of large and small carbon residues within the ceramic, thus affecting its properties. Furthermore, the ceramic in Comparative Example 2, after grinding and polishing, shows... Figure 3As shown, some of the larger soft carbon tissues were removed, leaving many pits. Comparative Example 3 is a silicon carbide ceramic prepared using phenolic resin binder. Due to the lack of EpsA-O extracellular polysaccharide to regulate the silica diffusion channels, the silica diffusion channels in the sample exhibit problems of being either too wide or too narrow. This results in more residual silicon in areas where the silica diffusion channels are too wide, and the silicon carbide particles are not linked together. In areas where the silica diffusion channels are too narrow, continuous silica diffusion is difficult, thus forming pores. Figure 3 The results show that the residual silicon is large in size, has a high content and uneven distribution, and there are also a large number of pores in the material, which affects the mechanical properties of the ceramic.

[0159] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0160] The embodiments described above are merely illustrative of several implementation methods of this application, and while the descriptions are specific and detailed, they should not be construed as limiting the scope of the application. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of this application, and these modifications and improvements all fall within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the appended claims, and the specification can be used to interpret the content of the claims.

Claims

1. A method for preparing silicon carbide ceramics with microbial aging assistance, characterized in that, Includes the following steps: A clay blank is obtained by mixing and refining a mixture comprising silicon carbide, carbon materials, Bacillus subtilis spore powder, nitrogen source nutrients, carbon source nutrients, binder, curing agent, and solvent; wherein the mass percentage of silicon carbide in the mixture is 50% to 75%, and the mass percentage of Bacillus subtilis spore powder is 1% to 4% of the mass of silicon carbide; the biosecurity number of the Bacillus subtilis spore powder is CICC 10089; After aging the clay blank, the viscosity of the clay blank is reduced to 200 Pa·s to 340 Pa·s; then the clay blank is subjected to solidification molding and adhesive removal treatment in sequence to obtain the raw blank. The green body is subjected to silicon infiltration treatment to obtain the silicon carbide ceramic; The method for preparing the clay blank includes: The silicon carbide, the carbon material, and the Bacillus subtilis spore powder are mixed to obtain a mixed powder. A first mixture containing the binder, the curing agent, and the first solvent is mixed with a second mixture containing the nitrogen source nutrient, the carbon source nutrient, and the second solvent to obtain a mixed solution; After spraying nutrient solution into the mixed powder, the mixed solution is then added to mix and knead the mud to obtain the mud blank. The nutrient solution includes water, glycerol and peptone.

2. The method for preparing silicon carbide ceramics with microbial aging assistance as described in claim 1, characterized in that, The method for preparing silicon carbide ceramics with microbial aging assistance satisfies at least one of the following conditions: (1) The mixing and refining speed is 30 rpm to 42 rpm and the time is 20 min to 60 min; (2) The thickness of the clay blank is 2mm~3mm; (3) The environmental conditions for the aging process are: temperature 30℃~40℃, humidity ≥90%RH, aging time 18h~40h, and oxygen volume concentration 18%~22%; (4) During the aging process, the clay blanks are laid on a screen; (5) The pH of the clay blanks during the aging process is 6.5~7.5; (6) The curing molding adopts injection molding, the temperature of injection molding is 140℃~200℃, the holding time is 1h~10h, and the injection pressure is 0.1MPa~5MPa; (7) The temperature of the glue removal treatment is 900℃~1100℃, the heat preservation time is 1h~4h, the heating rate is 1℃ / min~5℃ / min, and the atmosphere is a protective atmosphere.

3. The method for preparing silicon carbide ceramics with microbial aging assistance as described in claim 1, characterized in that, The method for preparing silicon carbide ceramics with microbial aging assistance satisfies at least one of the following conditions: (1) The nitrogen source nutrient includes at least one of peptone, yeast extract and ammonium sulfate; (2) The nitrogen source nutrient includes peptone and yeast extract, and the mass ratio of peptone to yeast extract is (5~8):(2~5). (3) The carbon source nutrient includes at least one of glucose and glycerol; (4) The carbon material includes at least one of graphite, carbon powder and carbon black; (5) The adhesive includes at least one of phenolic resin and epoxy resin; (6) The curing agent includes at least one of hexamethylenetetramine and methylhexahydrophthalic anhydride; (7) The solvent includes a first solvent and a second solvent, wherein the first solvent is used to dissolve the binder and the curing agent, and the first solvent includes ethylene glycol; the second solvent is used to dissolve the carbon source nutrient and the nitrogen source nutrient, and the second solvent includes at least one of glycerol, polyethylene glycol and propylene glycol; (8) The silicon carbide includes a first silicon carbide and a second silicon carbide; wherein the volume average particle size of the first silicon carbide is 0.5 μm to 5 μm, and the volume average particle size of the second silicon carbide is 20 μm to 100 μm; the mass ratio of the first silicon carbide to the second silicon carbide is 1:(1~4). (9) The mass of the nitrogen source nutrient in the mixture is 60% to 150% of the mass of the Bacillus subtilis spore powder; (10) The mass of the carbon source nutrient in the mixture is 80% to 200% of the mass of the Bacillus subtilis spore powder; (11) The mass of the carbon material in the mixture is 12% to 24% of the mass of the silicon carbide; (12) The mass of the binder in the mixture is 3.5% to 11.5% of the mass of the silicon carbide; (13) The mass of the curing agent in the mixture is 9% to 12% of the mass of the adhesive.

4. The method for preparing silicon carbide ceramics with microbial aging assistance as described in claim 1, characterized in that, The mixture also contains a lubricant.

5. The method for preparing silicon carbide ceramics with microbial aging assistance as described in claim 4, characterized in that, The lubricant satisfies at least one of the following conditions: (1) The lubricant includes at least one of paraffin wax, stearic acid and oleic acid; (2) The mass percentage of the lubricant in the mixture is 1% to 3%.

6. The method for preparing silicon carbide ceramics with microbial aging assistance as described in claim 1, characterized in that, The silicon infiltration process includes: laying silicon particles on the green blank, heating and melting them, and then cooling to obtain the silicon carbide ceramic.

7. The method for preparing silicon carbide ceramics with microbial aging assistance as described in claim 6, characterized in that, The silicon infiltration process satisfies at least one of the following conditions: (1) The volume average particle size of the silicon particles is 0.5 mm to 5 mm; (2) The amount of silicon particles added is 1 to 1.5 times the mass of the preform; (3) The heating temperature during the silicon infiltration process is 1500℃~1800℃, the holding time is 1h~6h, the heating rate is 2℃ / min~10℃ / min, and the vacuum degree is ≤50Pa.

8. The method for preparing silicon carbide ceramics with microbial aging assistance as described in claim 1, characterized in that, The method for preparing the clay blank satisfies at least one of the following conditions: (1) The mixed powder is formed by ball milling, wherein the ball-to-material ratio is (5~10):1, the ball milling speed is 100rpm~150rpm, and the time is 4h~8h; (2) The first mixture contains 45% to 50% by mass of the binder and 4.0% to 5.5% by mass of the curing agent, and the first solvent includes ethylene glycol; (3) The second mixture contains 10-15% nitrogen source nutrient and 15-20% carbon source nutrient by mass, and the second solvent includes at least one of glycerol, polyethylene glycol and propylene glycol; (4) The nutrient solution comprises water, glycerol, and peptone in a mass ratio of (2.90~2.99):(6.90~6.99):(0.01~0.05); (5) The volume of the nutrient solution sprayed onto each gram of the mixed powder is 0.05 mL to 0.07 mL; (6) The average volumetric particle size of the droplets formed by spraying the nutrient solution is 5 μm to 50 μm.

9. A silicon carbide ceramic, characterized in that, The silicon carbide ceramics were prepared using the method described in any one of claims 1-8, which is a microbial aging-assisted preparation method.

Citation Information

Patent Citations

  • Preparation method of honeycomb ceramic heat storage material

    CN107459335A

  • Preparation method of porous foamed silicon carbide ceramic

    CN108892531A